MASTERS’ DEGREE IN EDUCATIONAL MANAGERS IN THE REPUBLIC OF CYPRUS: PROGRAM ANALYSIS - Voyevutko, Nataliia (The Modern Higher Education Review, 2019)
The article analyzes the content of curricula for the training of education managers in the Republic of Cyprus. The peculiarities of the formation of the master’s degree programs at the Open University of Cyprus, the University of Frederic Cyprus, the European University of Cyprus, the University of Nicosia, the University of Naples, the International Institute of Management of Cyprus are considered. It has been found out that the programs include graduates of the baccalaureate of pedagogical specialties, as well as educators who already work at the positions of teachers, school directors, school counselors, education managers, heads of institutions providing educational services in vocational and continuing education institutions. The credit dimension of the programs is determined, which corresponds to 90 or 120 ECTS, where the content of compulsory and selective disciplines is formed in relation to 1/2. Obligatory disciplines have identified those that provide the ability to administer and explore education and provide a clear understanding of organizational theories, their ability to implement at schools and any other educational institutions; the ability to analyze current educational issues, to offer decisions and discuss the consequences of their making, to understand the dynamic environment in which the educational institutions and the education system operate in general, to investigate and analyze various models of document circulation in each educational institution and in the educational system on the whole. The content of selective disciplines forms the special knowledge of future managers, explains phenomena such as change design, leadership and innovative educational programs, theoretical models of effective education, and the study of strategic planning, accountability and responsibility issues.